2006
DOI: 10.1108/02652320610701717
|View full text |Cite
|
Sign up to set email alerts
|

A logit analysis of electronic banking in New Zealand

Abstract: Financial institutions have been adopting internet banking since the mid 90s, predominantly due to lower operating costs associated with internet banking, and pressure from non-banks interested in entering the internet banking market. In addition, customers utilizing internet banking facilities are increasing, as the cost savings on transactions over the internet are substantial (Mols, 1998;Sathye, 1999). Internet banking enables speedy transactions, access, time and money savings through providing free paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 39 publications
6
121
0
4
Order By: Relevance
“…The results of the multiple regression analysis signal that there is variation in the effect of e-banking factors on customer satisfaction and empirical evidence in this research suggests that adoption of e-banking factors have a significant degree of influence on customer satisfaction. This empirical evidence has provided significant support for the electronic banking literature, which substantively advocates that e-banking factors have an influence on customer satisfaction (Jayawardhena and Foley, 2000;Robinson, 2000;Pikkarainen et al, 2004;Gan et al, 2006;Hua, 2009;Wise and Ali, 2009). …”
Section: The E-banking Functionality Factors Has a Positive Significamentioning
confidence: 72%
See 1 more Smart Citation
“…The results of the multiple regression analysis signal that there is variation in the effect of e-banking factors on customer satisfaction and empirical evidence in this research suggests that adoption of e-banking factors have a significant degree of influence on customer satisfaction. This empirical evidence has provided significant support for the electronic banking literature, which substantively advocates that e-banking factors have an influence on customer satisfaction (Jayawardhena and Foley, 2000;Robinson, 2000;Pikkarainen et al, 2004;Gan et al, 2006;Hua, 2009;Wise and Ali, 2009). …”
Section: The E-banking Functionality Factors Has a Positive Significamentioning
confidence: 72%
“…With the exception of cash withdrawals, internet banking gives customers access to almost any type of banking transaction at the click of a mouse (De Young, 2001). Indeed the use of the internet as a new alternative channel for the distribution of financial services has become a competitive necessity instead of just a way to achieve competitive advantage with the advent of globalization and fiercer competition (Flavián et al, 2004;Gan and Clemes, 2006). Banks use online banking as it is one of the cheapest delivery channels for banking products (Pikkarainen et al, 2004).…”
Section: Definition Of the E-bankingmentioning
confidence: 99%
“…In consonance to these findings, different studies on adoption of e-banking have also reported employment or occupational status (Gan et al, 2006) and level of income (Adapa et al, 2009) Vol. 6, No.…”
Section: Discussionmentioning
confidence: 76%
“…Several works (Akinci et al, 2004;Laforet & Li, 2005;Wan et al, 2005, Hernandez & Mazzon, 2007 have attempted to identify factors that possibly influence peoples' adoption of e-banking services. For example, Gan et al (2006) employed a logit model to examine consumers' choices between electronic banking and non-electronic banking in New Zealand. Cairo and Staten (1999) also used a logistic regression model to investigate the preferences of consumers using debit cards, credit cards, and cash for gasoline purchases.…”
Section: Introductionmentioning
confidence: 99%
“…In the view of [20] social media marketing SMM "is a term which describes the actual acts of using social networks for marketing purpose". [21] notes that Social media marketing focus on people not product.…”
Section: Concept Of Social Media Marketingmentioning
confidence: 99%